THE EFFECT OF ACTIVE LEARNING ON STUDENTS’ SUCCESS AND INFORMATION RETENTION IN ADVANCED MATHEMATICS - Nurbavliyev, O.; Gur, T.; Аlmas A.; Abdulbaki, M. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Mathematical analysis subjects are complicated and intricately related to each other. Hence, the retention skills of math topics and contents play a considerable role in the learning process. This study aims to examine the effectiveness of active learning (AL) on student academic achievement and information retention skills in the learning process of mathematical analysis course. The related hypothesis is that AL is more effective than regular conventional learning in success and keeping students’ retention skills. AL implementation was conducted among first-year students (200) and lasted for 14 weeks during the spring semester of the academic year. We used an academic expert of the education faculty at a Kazakhstani University to instruct the lectures, and we used a pre-test and post-test design, and scores were interpreted statistically. Results indicated a significant effect of AL students’ achievement and retention skills in mathematical analysis course.